1s2p RIXS Calculations for 3d Transition Metal Ions in Octahedral Symmetry. (24th June 2018) - Zimmermann, Patric; Hunault, Myrtille O. J. Y.; de Groot, Frank M. F.
Abstract : We present a series of 1s2p resonant inelastic X-ray scattering (RIXS) calculations for 3d transition metal ions in octahedral symmetry covering each ground state between 3d 0 and 3d 9 . The calculations are performed in octahedral (O h ) symmetry using the crystal field multiplet theory. We discuss the crystal field effects and the selection rules with respect to the 1s2p RIXS pre-edge and compare their final state energies with the corresponding 2p X-ray absorption spectrum (XAS). The calculations provide a detailed understanding of 1s2p RIXS and serve as a basis for the future analysis of experimental spectra and also as a starting point for calculations that add additional channels including the nonlocal peaks.